Pemanfaatan Adsorben Serbuk Marmer dan Batuan Manure Ayam Petelur terhadap Persentase Gas Bio - Mohamad Imam Zarkasi; Mochammad Junus (Bioscientist : Jurnal Ilmiah Biologi, 2022)
This study aims to determine the effect of the adsorbents of marble powder and manure rock of laying hens on the percentage of bio-gas content, and to determine the optimization of the adsorbent treatment of manure rock of laying hens and marble powder in producing the percentage of bio-gas content and reducing the amount of bio-gas content other than CH4. The research material used was chicken manure rock and marble powder. The research method used was an experiment with RAL (completely randomized design), which consisted of 4 treatments and 4 replications. The treatment is without using adsorbents; 100% laying hen manure rock; 100% marble powder; and 50% marble powder + 50% manure rock laying hens. The variables observed in this study include the volume and time required for methane gas to flow through the adsorbent, the time required for methane gas to pass through the adsorbent to the gas-holding balloon as a sample, and the gas content in methane gas before purification, the percentage levels of CO2, CH4, O2, and N2. The results showed that the use of marble powder and manure rock adsorbents for laying hens on the percentage of biogas content gave no significant difference (P > 0.05) to the percentages of CH4, O2, and N2 gases, but gave a significant difference (P <0.05 ) to the percentage of CO2 gas of 11.33% was found in the P2 treatment which used 100% marble powder adsorbent. P2 treatment was able to reduce CO2 levels by 59.70%. It can be concluded that the greater the CH4, the better the calorific value and is inversely proportional to CO2.